A Case Study: Negative Effects of Unscheduled Appointment System to Physiotherapists and Paediatric Patients - Triana Karnadipa (Media Kesehatan Masyarakat Indonesia, 2020)
Community-Based Rehabilitation (CBR) units are growing in developing countries, including Indonesia. However, patient safety measures in CBR units have not yet been conducted, especially regarding flexible, unscheduled appointment system. This study aims to evaluate the unscheduled appointment system as a cause of errors in the care delivery of a CBR unit for children with disabilities in Makassar city. This case study conducted 278-hours observations and three structured interviews. The observation findings, encoded interview findings, field notes, and self-reflective notes were triangulated and link thematically. Four key findings were illustrated in an explorative model. The CBR unit implements a day-based scheduling system without time slots. Working in this system, the therapists experienced random visits, long waiting times, and excessive workload as a result of this flexible scheduling system. Significant risks of human errors and patient safety were revealed due to these consequences. As flexible scheduling systems produce more negative effects to the therapists and children, it is suggested that a CBR unit or a health care unit implement a scheduled appointment system with timeslots to achieve prudent healthcare.